Long-term effects of the Paraguayan War (1864 - 1870): From male scarcity to intimate partner violence - Barbara Boggiano (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
This paper investigates the long-term effects of the Paraguayan War (1864-1870) on intimate partner violence. The identification of these causal effects relies on a novel historical dataset from which I exploit the distance from municipalities to military camps during the war. Over 130 years later, the likelihood of intimate partner violence is still 5.54 percent higher than average in municipalities that were more heavily affected by the war. The loss of life among men led to female-biased sex ratios and defined Paraguay as the 'country of women'. However, I show that, contrary to conventional wisdom, female-biased sex ratios are not the only driver of the long-term effects of the war. Instead, the main transmission channel is the relative status of females within the household. Male scarcity leads to atypical status inconsistencies within the household that do not respect traditional gender roles and induces intimate partner violence that is transmitted across generations.
Keywords: I15; N36; O15; Z10; 330; intimate partner violence; long-term effects; gender norms; male scarcity